ARGILA SATURADA COM ÍONS COBRE APLICADA NA REMOÇÃO DE CORANTE E SEU REUSO COMO PIGMENTO - Rocha, Maria Lidia Morais da (2021)
In this study, a natural clay from the Guarapuava region was satured with copper ions by ion exchange and applied to remove violet dye from an aqueous medium, and later use it as hybrid pigment. The precursor and modified clay were characterized by X-ray diffraction (XRD), X-ray fluorescence (EDXRF), vibrational (FTIR) and electronic (UV-VIS) spectroscopy, Zeta potential (), scanning electron microscopy (SEM) and colorimetry (CIE L*a*b*), making it possible to identify the presence of copper ions intercalated and on the clay surface. The adsorption tests were carried out evaluating the effects of the initial dye concentration and contact time. The experimental equilibrium data were adjusted for the linearized isotherms of Freundlich an Lagmuir. The optimized kinetic data for each adsorption model were adjusted to the pseudo-first order and pseudo-second order models. Langmuir´s isothermal and pseudo-second order kinectics models were the most suitable to describe the adsortive process. The modification with copper ions promotes an increase in the adsorptive capacity in relation to natural clay. After the dye removal step, the materials were again characterized, and the presence of the dye on the clay surface was identified. Tests applied as inorganic and hybrid pigments, show good compatibility with commercial white paint. And in the form of compacted powder the have an efficient antibacterial action.